Psychiatric mental health nurse practitioner student knowledge and perceptions of pharmacogenetic testing - Kaltenrieder, Corrina M.; White, Michelle Marie; Cheek, Dennis J. (Frontiers in Genetics, 2023)
Abstract Psychotropic medications are typically prescribed in a trial-and-error fashion, and some providers are beginning to utilize pharmacogenetic testing (PGx) as a supplemental prescribing tool in treatment decision making. PGx testing shows potential in enhancing provider insights into personalized prescribing for patients by examining genetic information related to drug metabolism. Literature points to providers’ lack of knowledge in PGx interpretation as a main barrier, including psychiatric mental health nurse practitioners (PMHNPs). The aim of this study was to measure a difference, if any, in the knowledge and perceptions of PGx after implementation using a pre-post design. This study implemented an educational intervention on graduate nursing students (n = 15). Data were collected by using a pre- and post-interventional questionnaire. Results demonstrated a significant difference in findings related to students’ knowledge (p < .001), students’ skills related to pharmacogenetics, (p < .001), as well as students’ perceived ability to implement pharmacogenetics into their practice, (p = 0.028). The authors propose that the knowledge gained from the study demonstrates the importance of introducing PGx education into the PMHNP curricula and to prepare future PMHNPs to confidently utilize PGx in their clinical practice.